PROFIL PENDERITA PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) YANG DIRAWAT INAP DI RSUD ARIFIN ACHMAD PROVINSI RIAU TAHUN 2013 - Tuko Gustari Lisa; Azizman Saad; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
AbstractChronic Obstructive Pulmonary Disease (COPD) is chronic inflammatorydisease of the lungs marked by breath and obstruction of air flow is persistent andprogressive as a response to the particles or gases dangerous. The severity of COPDdepends on its exacerbations and comorbidities of each individual. The purpose ofthis study to determine the profile of COPD patients who are hospitalized at ArifinAchmad Hospital in 2013 by age, sex, occupation, smoking history, chief complaint,additional complaints and a history of exacerbations. The study was conducted inNovember-December 2014. The study was conducted in November-December 2014.The study sample as many as 80 people. The data collected is secondary dataobtained from medical records. The results showed that COPD patients who arehospitalized at Arifin Achmad Hospital in 2013 based on age are more common inthe age of 61-70 years as many as 29 people (36.3%), based on gender men are oftensuffer ppok 87,5 people ( 70 % ), based on the work of people with COPD who foundwork as self-employed as many as 33 people (41.25%),based on a history of smoking,COPD patients who had a positive smoking history as many as 50 people (62.5%),the main complaint is shortness of breath are found as many as 69 people (86.25%),additional complaints were most common are chest pain and headaches as many as20 people (21.3%) and COPD patients who are hospitalized with a history ofexacerbations most 0-1 times per year as many as 55 people (68.75%).Keywords: COPD, patient profile